Unilateral atlanto-axial fractures in near side impact collisions: An under recognized entity in cervical trauma - Andrew M Lozen; Jonathan Pace; Narayan Yoganandan; Frank A Pintar; Joseph F Cusick (Journal of Craniovertebral Junction and Spine, 2014)
Objective: Nearside impact collisions presenting with lateral mass fractures of atlanto-axial vertebrae contralateral to the impact site represents a rare fracture pattern that does not correlate with previously described injury mechanism. We describe our clinical experience with such fractures and propose a novel description of biomechanical forces involved in this unique injury pattern. The findings serve to alert clinicians to potentially serious consequences of associated unrecognized and untreated vertebral artery injury. Material and Methods : In addition to describing our clinical experience with three of these fractures, a review of Crash Injury Research and Engineering Network (CIREN) database was conducted to further characterize such fractures. A descriptive analysis of three recent lateral mass fractures of the atlanto-axial segment is coupled with a review of the CIREN database. A total of 4047 collisions were screened for unilateral fractures of atlas or axis. Information was screened for side of impact and data regarding impact velocity, occupant injuries and use of restraints. Results: Following screening of unilateral fractures of atlas and axis for direct side impacts, 41 fractures were identified. Cross referencing these cases for occurrence contralateral to side of impact identified four such fractures. Including our recent clinical experience, seven injuries were identified: Five C1 and two C2 fractures. Velocity ranged from 14 to 43 km/h. Two associated vertebral artery injuries were identified. Conclusions: Complexity of the atlanto-axial complex is responsible for a sequence of events that define load application in side impacts. This study demonstrates the vulnerability of vertebral artery to injury under unique translational forces and supports the use or routine screening for vascular injury. Diminished sensitivity of plain radiography in identifying these injuries suggests that computerized tomography should be used in all patients wherein a similar pattern of injury is suspected.